STEM Parents and Women in Finance. Issue 2 (1st April 2018) - Adams, Renée B.; Barber, Brad M.; Odean, Terrance
Abstract : "STEM parents" refers to parents who work in a science, technology, engineering, or mathematics field. Using survey data from CFA Institute members, we show that parental careers differentially affect the future career choices of girls and boys. Among CFA Institute members, women are more likely to have a STEM parent (particularly a STEM mother) than men. Relative to the base rates at which girls and boys become CFA Institute members, STEM mothers increase the girls' rate by 48% more than the boys' rate; STEM fathers increase the girls' rate 29% more than the boys' rate. Our findings are consistent with the hypothesis that early role models, particularly female role models, influence women's choice of a finance career. Abstract : Disclosure: The authors report no conflicts of interest. Editor's Note Submitted 17 July 2017 Accepted 5 December 2017 by Stephen J. Brown